Glucocorticoid induction of epinephrine synthesizing enzyme in rat skeletal muscle and insulin resistance. - Kennedy, B (1993)
Rat skeletal muscle contains two enzymes which can make epinephrine: phenylethanolamine N-methyltransferase (PNMT) and nonspecific N-methyltransferase. We studied the time-course and mechanism by which the glucocorticoid dexamethasone increases muscle PNMT activity. We also examined the hypothesis that increased muscle E synthesis may contribute to glucocorticoid-induced insulin resistance. Dexamethasone (1 mg/kg s.c. for 12 d) increased muscle PNMT activity seven-fold but did not change NMT activity. Immunotitration with an anti-PNMT antibody indicated that the PNMT elevation was due to increased numbers of PNMT molecules. Dexamethasone rapidly increased PNMT activity and this elevation was largely maintained 6 d after glucocorticoid treatment stopped. Muscle epinephrine levels were transiently elevated by dexamethasone. Dexamethasone-treated rats had elevated insulin levels after a glucose load, and chronic administration of the PNMT inhibitor SKF 64139 reversed this increase. Chronic SKF 64139 improved glucose tolerance in normal rats. Dexamethasone induced muscle synthesis of the epinephrine-forming enzyme PNMT. A PNMT inhibitor lowered insulin levels in glucocorticoid-treated rats and glucose levels in untreated rats. These findings are compatible with antagonism of insulin-mediated glucose uptake by epinephrine synthesized in skeletal muscle.